DESIGNING ANIMAKER AS INSTRUCTIONAL MEDIA IN LEARNING READING DESCRIPTIVE TEXT AND RECOUNT TEXT FOR TENTH GRADE STUDENTS AT MA DARUL FALAH - Ismatul Maula (Language-Edu, 2021)
AbstractThe current study aims to design animaker as instructional media for teaching reading to solve students’ problems in reading descriptive text and recount text at MA Darul Falah. The study used Design and Development (D&D) research design followed by Richey & Klein (2007) and Alessi & Trollip (2001) model with four stages; those are planning, designing, developing and validating. The planning stage was finding students’ difficulties learning reading by interviewing students and observing classroom situation. The designing stage was observing syllabus and text book used in tenth grade of senior high school. Developing stage was the process of producing instructional media using animaker. The Validating stage used internal and external validation. Internal validation was the validation of animaker video by experts using questionnaire as the instrument. Besides, external validation was testing the product to students by conducting try out to know the compatibility of animaker in solving students’ problems in learning reading descriptive and recount text. The study produced animation videos of descriptive and recount text that could complete the existence of textbook when the material was difficult and boring. Students’ could understand reading text easily using animaker. Furthermore, animaker could motivate students to learn reading because animaker was designed using innovative tolls.Keywords: animaker, descriptive and recount text, reading